If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = -6 + 7x Solving 5x = -6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 5x + -7x = -6 + 7x + -7x Combine like terms: 5x + -7x = -2x -2x = -6 + 7x + -7x Combine like terms: 7x + -7x = 0 -2x = -6 + 0 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| x=2(90-x)-12 | | 97-w=170 | | 3(3x-9)+14x= | | 535+.21x=850 | | 230-x=15 | | 7(x+5)=6x+45 | | 228+-x=75 | | 55+x+4x-5=180 | | 4.9t^2+10t-61=0 | | 3y-21=-28+2y | | 3u-5=8u-20 | | 5v+2=32 | | 24b-12=5b | | 350000=350000-.11x | | 3y+9=10y+30 | | x=(90-x)-12 | | X+.11=350000 | | 17-9x=71 | | 5/12=b/5 | | 8+3w=23 | | 3x+66=360 | | 3u-5=8u-28+8 | | A^2(5a+2)(a+2)=0 | | X^2+4x-6=12 | | 8=3m-16 | | k^3-k^2-4k+4=0 | | x^2+5x-6=12 | | X-3=180 | | -13=y-4 | | x^4+5x-6=12 | | (3.250+2.75)*2= | | (+6+-2)*-3= |